Faktor-Faktor Yang Mempengaruhi Kenaikan Berat Badan Pada Akseptor KB Suntik 2 Bulan (Gestin F2) Di Wilayah Kerja Puskesmas Purwoyoso Semarang - Yosi Puspitasari; Tia Nurhanifah; Kristina Maharani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Introduction: Combined injection contraception can be an option for all women of reproductive age who have poor adherence. Most acceptors often complain that after using 2 months of injectable birth control they feel that they have gained weight. Many have switched to other birth control methods because of weight gain. Objective: to determine the factors that influence weight gain in 2-month injection family planning acceptors (Gestin F2) in the Working Area of the Purwoyoso Health Center, Semarang. Methods: The research method used was an analytic survey with a cross-sectional approach. Sample: The population in this study were 45 people who were in the Working Area of the Purwoyoso Health Center Semarang with a sample of 44 respondents. Data collection was carried out using a questionnaire. Data analysis used is Chi-square analysis. Results: that physical activity had an effect on weight gain, while husband's support, duration of use of family planning, diet, age, history of use of family planning had no significant relationship with weight gain in respondents who accepted the 2-month injection of family planning (Gestin F2) in the Purwoyoso Public Health Center, Semarang.